THE IMPACT OF THE USE OF FINANCIAL LEVERAGE ON LIQUIDITY BANKING, AN ANALYTICAL STUDY FOR THE COMMERCIAL BANK OF IRAQ FOR THE PERIOD (2004-2022) - Alnaqshabandy, Firas (Humanities Journal of University of Zakho, 2024)
This study sought to know the effect of financial leverage on bank liquidity through data obtained from the financial reports issued by the Commercial Bank of Iraq during the period (2004-2022) because the aforementioned bank was the research sample. The research relied on the analytical approach using the influence model of the research variables through the (SPSS25) program. The study reached several results, including the presence of an impact of financial leverage on bank liquidity. One of the most important research proposals is achieving a balance between liquidity and entering into investment projects to achieve profitability and achieve banking goals. In order to reduce the risks resulting from banking activities in the future, it has been proposed to follow the principles of universal and private banking. In the field of diversifying the loans granted, which would reduce banking risks, especially with regard to the loans granted.